Improving thermoelectric performance of indium thiospinel by Se- and Te-substitution. Issue 11 (4th March 2021) - Wyżga, Paweł; Grimm, Sven; Garbe, Valentin; Zuñiga-Puelles, Esteban; Himcinschi, Cameliu; Veremchuk, Igor; Leithe-Jasper, Andreas; Gumeniuk, Roman
Abstract : Substitution of S by Se or Te in the In2.67 S4 thiospinel was accompanied by an improvement of the charge carrier concentration and a reduction of the effective electron mass, which resulted in the enhancement of the thermoelectric figure of merit ZT . Abstract : A structural and thermoelectric study of the polycrystalline Se- and Te-substituted In2.67 S4 thiospinels was performed. The obtained In2.67 S4− x Se x (0 ≤ x ≤ 0.5) and In2.67 S4− y Te y (0 ≤ y ≤ 0.15) samples were single phase and the solubility limits of Se and Te were not reached. A comprehensive phase analysis based on powder X-ray diffraction and Raman spectroscopy, as well as Rietveld refinements, confirmed that Se/Te-incorporation into the structure of binary β-In2.67 S4 ( x = 0) favors the formation of the cubic α-modification for x > 0.15 and y ≥ 0.05. Moreover, both cubic and tetragonal phases were shown to coexist in the In2.67 S3.9 Se0.1 specimen. The Se/Te-for-S substitution strongly influenced electronic transport properties, leading to an increase of the charge carrier concentration and thus, a reduction of the electrical resistivity and Seebeck coefficient. A decrease of charge carrier mobility, observed previously upon the stabilization of the α-phase, was partially counterbalanced by a reduction of effective electron mass, as revealed by the electronic structure calculations. This resulted in the enhancement of the power factor PF > 10 −4 W m −1 K −2 above RT for In2.67 S3.9 Se0.1 and In2.67 S3.5 Se0.5 thiospinels in comparison to pristine In2.67 S4 . Combination of such an effect with the decreased thermal conductivity ( i.e., < 1.5 W m −1 K −1 above RT) led to the improvement of the thermoelectric figure of merit by factor of 2.5 in In2.67 S3.5 Se0.5 .